2020
DOI: 10.1158/0008-5472.can-20-0034
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte-Derived Leukemia-Associated Macrophages Facilitate Extramedullary Distribution of T-cell Acute Lymphoblastic Leukemia Cells

Abstract: Macrophages play important roles in both physiological and pathological processes and arise from successive waves of embryonic and adult hematopoiesis. Monocyte-derived macrophages (MOMF) exert distinct functions under pathological conditions, and leukemia-associated macrophages (LAM) show considerable diversities in activation and functional phenotype. However, their origin and pathological roles have not been well elucidated. Here we used wild-type (WT) and CCR2-/mice to study the pathological roles of monoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…These findings suggest that tumor-associated myeloid cells may activate FAK and PYK2 in T-ALL cells not only through integrin signaling, but also through additional pathways. A previous study reported that Vegfa and Il1b transcripts are elevated in leukemia-associated macrophages in a NOTCH1-induced model of T-ALL (57), suggesting secreted myeloid factors could promote FAK/PYK2 activation in T-ALL cells. Thus, a better understanding of the mechanisms by which tumor-associated myeloid cells activate FAK and PYK2 signaling and how these pathways contribute to T-ALL progression could reveal therapeutic opportunities in T-ALL.…”
Section: Discussionmentioning
confidence: 98%
“…These findings suggest that tumor-associated myeloid cells may activate FAK and PYK2 in T-ALL cells not only through integrin signaling, but also through additional pathways. A previous study reported that Vegfa and Il1b transcripts are elevated in leukemia-associated macrophages in a NOTCH1-induced model of T-ALL (57), suggesting secreted myeloid factors could promote FAK/PYK2 activation in T-ALL cells. Thus, a better understanding of the mechanisms by which tumor-associated myeloid cells activate FAK and PYK2 signaling and how these pathways contribute to T-ALL progression could reveal therapeutic opportunities in T-ALL.…”
Section: Discussionmentioning
confidence: 98%
“…Wright staining was performed following the standard protocols. 36 The morphology of cells was detected under a light microscope (AXIO Observer A1, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…This change in the hematopoietic topographic hierarchy during inflammation entails important biological, diagnostic and therapeutic implications. Monocytes from extramedullary tissues, such as the spleen, belong to the inflammatory subset (Ly-6C high ) and express proinflammatory factors, including reactive oxygen species and proteases (80,133,134). They accumulate in developing lesions, favoring an enhanced lipid intake and hypercholesterolemia that lead to atheroma progression.…”
Section: Pros and Cons Of Splenectomy: Clinical Impact In Atherogenesmentioning
confidence: 99%